Pengaruh Akuntabilitas dan Transparansi Laporan Keuangan Terhadap Kepercayaan Muzakki pada BAZNAS Kabupaten Tasikmalaya - Taniari; Rizky Ridwan (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
Abstract : This study aims to analyze the influence of accountability and transparency of financial reports on the trust of muzakki in BAZNAS Tasikmalaya Regency. This study uses a quantitative approach with an associative method. The study population is the Muslim community in Tasikmalaya Regency who have paid zakat and are aware of the existence of BAZNAS Tasikmalaya Regency. The research sample consisted of 100 respondents selected using purposive sampling techniques. The analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination with the help of the SPSS version 30 program. The results of the study show that accountability has a positive and significant effect on the trust of muzakki. In addition, transparency also has a positive and significant effect on the trust of muzakki. In addition, accountability and transparency have a positive and significant effect on the trust of muzakki. These findings indicate that improving the quality of accountability and information transparency in the management of zakat funds is an important factor in building and increasing the trust of muzakki. Towards BAZNAS Tasikmalaya Regency Keywords: Accountability, Transparency, Financial Reports, Zakat Payers' Trust, Tasikmalaya Regency BAZNAS